The melancholic irony of Kierkegaard - Câmpean, Flaviu-Victor (Hybris, 2016)
The Socratic truth is in no way inferior to the Christian one in Kierkegaard’s view. The fundamental difference between the two is that whereas the later develops by means of a donation and of a specific dialectic as such, the former is hidden within the negative and anti- dialectical discourse of irony. We can therefore maintain that irony always pertains to the melancholic dimension of existence. My work aims to consider irony as a melancholic negativity, insofar as it is closely related to the demonic silence and void and as it rejects the wholeness of philosophical language. Sickness and health, symptom and remedy, the Kierkegaardian irony is melancholic because it perpetually suffers from its own re-opened wound, which allows us to interpret it from a psychoanalytical standpoint. Thus, the affinity between Kierkegaard and psychoanalysis sustains a Lacanian approach to the melancholic irony, in order to clarify its function in pinpointing the “real” truth of existence through a resistance to language.